Oral cysteamine as an adjunct treatment in cystic fibrosis pulmonary exacerbations: An exploratory randomized clinical trial - Devereux, Graham (PLoS One, 2020)
BACKGROUND: Emerging data suggests a possible role for cysteamine as an adjunct treatment for pulmonary exacerbations of cystic fibrosis (CF) that continue to be a major clinical challenge. There are no studies investigating the use of cysteamine in pulmonary exacerbations of CF. This exploratory randomized clinical trial was conducted to answer the question: In future pivotal trials of cysteamine as an adjunct treatment in pulmonary exacerbations of CF, which candidate cysteamine dosing regimens should be tested and which are the most appropriate, clinically meaningful outcome measures to employ as endpoints? METHODS AND FINDINGS: Multicentre double-blind randomized clinical trial. Adults experiencing a pulmonary exacerbation of CF being treated with standard care that included aminoglycoside therapy were randomized equally to a concomitant 14-day course of placebo, or one of 5 dosing regimens of cysteamine. Outcomes were recorded on days 0, 7, 14 and 21 and included sputum bacterial load and the patient reported outcome measures (PROMs): Chronic Respiratory Infection Symptom Score (CRISS), the Cystic Fibrosis Questionnaire–Revised (CFQ-R); FEV(1), blood leukocyte count, and inflammatory markers. Eighty nine participants in fifteen US and EU centres were randomized, 78 completed the 14-day treatment period. Cysteamine had no significant effect on sputum bacterial load, however technical difficulties limited interpretation. The most consistent findings were for cysteamine 450mg twice daily that had effects additional to that observed with placebo, with improved symptoms, CRISS additional 9.85 points (95% CI 0.02, 19.7) p = 0.05, reduced blood leukocyte count by 2.46x10(9) /l (95% CI 0.11, 4.80), p = 0.041 and reduced CRP by geometric mean 2.57 nmol/l (95% CI 0.15, 0.99), p = 0.049. CONCLUSION: In this exploratory study cysteamine appeared to be safe and well-tolerated. Future pivotal trials investigating the utility of cysteamine in pulmonary exacerbations of CF need to include the cysteamine 450mg doses and CRISS and blood leukocyte count as outcome measures. CLINICAL TRIAL REGISTRATION: NCT03000348; www.clinicaltrials.gov.